Do Recessions Accelerate Routine-Biased Technological Change? Evidence from Vacancy Postings - Hershbein, Brad; Kahn, Lisa B. (American Economic Review, 2018)
We show that skill requirements in job vacancy postings differentially increased in MSAs that were hit hard by the Great Recession, relative to less hard-hit areas. These increases persist through at least the end of 2015 and are correlated with increases in capital investments, both at the MSA and firm levels. We also find that effects are most pronounced in routine-cognitive occupations, which exhibit relative wage growth as well. We argue that this evidence is consistent with the restructuring of production toward routine-biased technologies and the more-skilled workers that complement them, and that the Great Recession accelerated this process. (JEL E24, E32, J24, J31, J63, L23, O33)